Determinan Akuntabilitas Pemerintahan Desa di Kabupaten Lombok Barat - Irwandi, Aziz; Sakti, Dwi Putra Buana; Pituringsih, Endar (E-Jurnal Akuntansi; Vol 31 No 5 (2021)DO - 10.24843/EJA.2021.v31.i05.p06, 2021)
This study aims to analyze the determinants of village government accountability in West Lombok Regency. The number of respondents used in the study was 60 people who served as the Village Head, Village Secretary, Village Treasurer, Village Consultative Body and Section Head in the Village office. Data collection was carried out by means of a questionnaire. The data analysis technique used multiple regression analysis. The results showed that Human Resource Competence and Accounting Reporting System had a negative effect on the Accountability of Village Government Performance. Meanwhile, Accounting Control and Organizational Culture have a positive effect on the Accountability of Village Government Performance. Keywords: HR Competencies; Accounting Controls; Accounting Reporting System; Organizational Culture; Accountability Of Local Government Performance.